Microbial synthesis of mammalian metabolites of spironolactone by thermophilic fungus thermomyces lanuginosus - Sreelatha, B.; Prasad, G. Shyam; Vankudoth, Koteswara Rao; Sivadevuni, Girisham (Steroids, 2018)
Mesophilic fungi are well recognized as models of mammalian drug metabolism. Thermophilic fungi remained unexplored despite having a unique mechanism of growing at higher temperatures and performing wide diverse reactions. The present investigation is directed to isolate a promising thermophilic fungal strain capable of biotransformation using spironolactone as a model drug. Two-stage fermentation protocol was followed for the process. The transformation of spironolactone was identified by HPLC and structure elucidation of the metabolites was done with the help of LC-MS/MS analysis and previous reports. A strain of Thermomyces lanuginosus isolated from decomposed banana peel waste was found to be most promising in transforming spironolactone to 4 metabolites viz.7α-thiospironolactone (M1) canrenone (M2), 7α-thiomethylspironolactone (M3) and 6β-OH-7α-thiomethylspironolactone (M4), the major mammalian metabolites reported previously. The synthesis of metabolites of spironolactone by T.lanuginosus similar to mammals clearly states that this fungus possess enzyme system similar to mammals. Hence, this fungus has the potential to use as a model organism for studying drug metabolism.